3345-2024 - IEEE Guide for Terminology and Classification of Electric Vehicle Charging Robots (IEEE, 2025)
The key terms and definitions for electric vehicle charging robots provided by this standard, which also proposes a general classification based on mobility and presents specific examples of robots for each type, are discussed in this standard.
Keywords: Battery charging stations (Electric vehicles)